Mosaicos de áreas protegidas e unidades de conservação. Dificuldades e desafios num arranjo de governança híbrida: o caso do Mosaico Bocaina - Costa, Antonio José Faria da (2015)
The main objective of this dissertation is to understand the functioning of a mosaic of protected areas – the Mosaic of Bocaina. It is said that today biodiversity conservation policies depend on the creation and proper management of protected areas. However, when the government created those protected areas in particular it was done by the time it was not legally required to consult the inhabitants of those places, which has led to numerous drawbacks for both sides and a real legal imbroglio when it comes to recognition of diffuse rights. The Mosaic of Bocaina was created by a decree of the Ministry of the Environment in late 2006. Since 2007 it has been trying to establish itself as a planning tool for integrated and participatory management of a set of protected areas. It also tries to mitigate and seeks possible solutions to historical land conflicts created by overlapping official and traditional territories. Through systematic analysis of documents produced as part of its Advisory Commitee, and the monitoring of debates of special themes by those actors interacting in that hybrid governance forum, we have tried to understand why certain themes advance and enter the agenda, being referred for competent decision-makers, and others can not even be processed, being blocked as soon as they appear. We have found that this process is a result of the configuration of dynamic forces of two advocacy coalitions vying, more than sharing, spaces in the area and always through polarized discussions. On the one hand, the pro-biodiversity coalition, which brings together managers of protected areas (both integral protection and sustainable use) and other actors whose focus is not always a conservationist agenda, but rather excluding one. On the other, pro-sociodiversity coalition, which fights for the adoption of a socioenvironmentalist and alternative agenda, which encompass the inclusion and ensuring the role of traditional communities in sustainable local development projects. We believe that this bias and difficulty in building consensus based on principles of collaboration and cooperation is a result of the complexity of governance management in hybrid forums like the Mosaic of Bocaina, where complexity is derived from the coexistence of values, preferences and interests often divergent. But we can also identify other specific factors, resulting of local characteristics and/or choices made by the collective of actors throughout the path. The huge asymmetry of information and power between the actors involved, for example, hinders the development of trust and reciprocity mechanisms. The adoption of a collegiate coordination, on the other hand, which eventually affects the emergence of a leadership or neutral body to serve as a mediator of the negotiations between the parties. The profound misunderstanding of possibilities – but, above all, also the limits – of mosaics of protected areas as territorial management tool within the broad Brazilian National System of Protected Areas generates conflict resolution expectations that depend on decisions made elsewhere, which ultimately frustrate and demobilize participants on both sides. The image of apparent apathy of federal and state environmental agencies, in turn, derived from the length of public processes, is bound to infund even more uncertainty in the relationship between the actors.